Buying Back The Right To Health: Legal And Policy Framework For Facilitating Access To Essential Medicines In Developing Countries - Mani, Tanvi (Journal of Sustainable Development Law and Policy, 2025)
The concept of public healthcare has perennially involved the institution of measures that are necessary for the prevention of large scale epidemics. This preventive approach embodies principles of sanitation, water purification and more recently vaccination. However, the advent of new strains of viruses and an unprecedented increase in the susceptible population has expanded the ambit of primary healthcare to include effective treatment. Especially in developing countries, treatment through affordable medicines is considered fundamental to the achievement of public health goals. Thus, there exists a humanitarian obligation on the international community and the respective governments of nations, to provide effective medication to those who cannot afford it, in the larger interest of maintaining a sense of equity in the sustenance of human life. This paper analyses relevant international treaties and domestic judicial interventions that could effectuate positive change in the formulation of international trade and intellectual property policies, with regard to healthcare, at national as well as an supranational levels. The paper argues for the transfer of the decision making powers, with regard to the distribution of drugs, from the private pharmaceutical industry to the governments of countries. This, it argues, would result in a shift in prioritization from profit making motives, to the universal realization of the right to health.